2017
DOI: 10.1080/00015458.2017.1287396
|View full text |Cite
|
Sign up to set email alerts
|

Triclosan-coated sutures for the prevention of surgical-site infections: a meta-analysis

Abstract: Further randomized studies are needed to confirm the role of TCS in specific surgical procedures and whether or not they are related with lower risk for mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…Our results support the findings of Konstantelias et al who concluded that triclosan-coated sutures were associated with a significantly lower risk of SSI when compared with standard sutures 32 61. In addition, the authors concluded that triclosan-coated sutures significantly reduced the risk of SSI in clean, clean-contaminated and contaminated surgery; in agreement with our findings 61. de Jonge et al reported a meta-analysis of 21 RCTs including 6462 patients, also concluding that triclosan-coated sutures significantly reduced the risk of SSI compared with standard sutures 32.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results support the findings of Konstantelias et al who concluded that triclosan-coated sutures were associated with a significantly lower risk of SSI when compared with standard sutures 32 61. In addition, the authors concluded that triclosan-coated sutures significantly reduced the risk of SSI in clean, clean-contaminated and contaminated surgery; in agreement with our findings 61. de Jonge et al reported a meta-analysis of 21 RCTs including 6462 patients, also concluding that triclosan-coated sutures significantly reduced the risk of SSI compared with standard sutures 32.…”
Section: Discussionsupporting
confidence: 93%
“…There have been 11 previous reviews in this topic area, the results of these reviews have been summarised in table 2 27 28 30–32 58–63. Our results support the findings of Konstantelias et al who concluded that triclosan-coated sutures were associated with a significantly lower risk of SSI when compared with standard sutures 32 61. In addition, the authors concluded that triclosan-coated sutures significantly reduced the risk of SSI in clean, clean-contaminated and contaminated surgery; in agreement with our findings 61.…”
Section: Discussionsupporting
confidence: 91%
“…Konstantelias et al [39] analyzed 30 studies (19 randomized, 11 non-randomized; 15,385 procedures) giving evidence that triclosan-coated sutures were associated with a lower risk of SSIs (risk ratio [RR] = 0.68; 95% confidence interval [CI] 0.57-0.81). Triclosan-coated sutures were associated with a lower risk for SSIs in high-quality randomized studies (Jadad score 4 or 5).…”
Section: Resultsmentioning
confidence: 99%
“…Nine meta-analyses were identified from database searching [28,29,[33][34][35][36][37][38][39] (Table 2). After the critical appraisal of all publications, Henriksen et al was selected as the latest meta-analysis that best matched the inclusion and exclusion criteria [28].…”
Section: Clinical Resultsmentioning
confidence: 99%